Pertanggungjawaban Hukum atas Wanprestasi Artis dalam Kontrak Eksklusif: Studi Kasus MD Entertainment melawan Rezky Aditya Studi Putusan Nomor 536/PK/Pdt/2015 - Muniratri Rachmita; Jingga Septira Arazea; Ibrahim Saleh Harahap; Naufal Jiro Rizayanto; Nigeel Jose Mourinho (PT. Hasba Edukasi Mandiri, 2025)
The dispute between PT MD Entertainment and Rezky Aditya in Supreme Court Decision No. 536 PK/Pdt/2015 highlights issues surrounding the enforcement of exclusive contracts between artists and production houses. This study examines the forms of breach of contract committed by the artist, the resulting legal liabilities, and the extent to which third parties may be held responsible for involving the artist despite knowing the existence of an exclusive agreement. Using a normative legal research method with statutory and case approaches, the analysis shows that the artist’s act of working with another production house while the contract was still in effect constitutes a breach that gives rise to compensation obligations. This decision underscores the importance of legal certainty and adherence to the principles of freedom of contract and pacta sunt servanda in the entertainment industry.